The feeding biology and potential impact of introduced giraffe (Giraffa camelopardalis) in the Eastern Cape Province, South Africa - Parker, Daniel Matthew (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2004)
Giraffe (Giraffa camelopardalis) are extralimital (non-native) to the Eastern Cape Province, South Africa yet they have and continue to be introduced to the region. Financial gain has arguably been the driving force behind these introductions as foreign tourists associate giraffe with Africa and the African wildlife experience. This raises a number of ethical, ecological and philosophical questions especially when it is considered that the impact of these browsers on the indigenous vegetation has remained largely unquantified. In this study I assessed the diet and potential impact of three populations of giraffe in the Eastern Cape Province between January 2002 and October 2003. The diet was assessed by both direct observations and faecal analysis. There was no significant difference (P > 0.05) between the results of the two methods of analysis, although direct observations appeared to be a superior method for assessing the diet of giraffe. The diet of giraffe in the Eastern Cape Province was similar to that within their native range with a deciduous species from the genus Acacia (Acacia karroo) being the most important component of the diet. However, giraffe in the Eastern Cape Province consumed more evergreen plant species than those within their native range. The relative lack of deciduous species in the Eastern Cape Province provides a likely explanation for such a result. Seasonal variation in the consumption of the most important species in the diet was evident and this was attributed to the deciduous nature of A. karroo and the seasonal growth of new shoots which were more palatable. The vegetation of the areas most commonly utilised by giraffe at each site was sampled using the point-centred-quarter method and the results related to the frequency of each species in the diet to calculate preference indices. Giraffe preference was strongest for A. karroo and this was attributed to the highly favourable chemical composition of the species. The browse utilisation of giraffe at each site was determined using the twig-length method and intake rates for the three most important species in the diet calculated using a pre-existing regression equation. Male giraffe fed at a higher rate than females. This was probably due to males adopting a "time-minimising" strategy to their feeding in order to allow more time for reproductive pursuits. Giraffe browse utilisation was highest where giraffe density was highest. However, several species were more heavily browsed than others even when giraffe density was low, suggesting that giraffe are capable of negatively affecting the indigenous flora of the province. I conclude that giraffe numbers should be reduced relative to property size in the Eastern Cape Province and that research into the impact of not only giraffe but the combined effects of giraffe and other extralimital herbivores on the indigenous flora and fauna be continued.
Keywords: Giraffe -- South Africa -- Eastern Cape; Animal-plant relationships -- South Africa -- Eastern Cape; Giraffe -- Food -- South Africa -- Eastern Cape